EPEN-09. IMPACT OF MOLECULAR SUBGROUP ON OUTCOME FOR INFANTS <12 MONTHS WITH INTRACRANIAL EPENDYMOMA - GERMAN EXPERIENCE FROM HIT2000, INTERIM-2000-REGISTRY AND I-HIT-MED REGISTRY. (4th December 2020) - Obrecht, Denise; Mynarek, Martin; von Hoff, Katja; Witt, Hendrik; Pajtler, Kristian W; Juhnke, B Ole; Warmuth-Metz, Monika; Bison, Brigitte; Kortmann, Rolf-Dieter; Timmermann, Beate; Pfister, Stefan M; Sahm, Felix; et al.
Abstract: BACKGROUND: For infant ependymoma (EP), decision for radiotherapy during first-line therapy is a dilemma. We analyzed therapy outcomes of EP patients younger than 12 months at diagnosis according to molecular subgroup. PATIENTS AND METHODS: Between 2001 and 2017, 30 patients with histological diagnosis of intracranial EP <12 months at diagnosis with DNA-methylation profiling available were registered in HIT-MED-studies/-registries. RESULTS: In 3/30, DNA methylation-based CNS tumor classification suggested a diagnosis other than EP or could not be assigned to a reference class. Of the remaining 27 tumors, 16 were classified as PF-A, 8 as RELA -fusion positive and 3 as YAP -fusion positive. Median age at diagnosis was 0.73 (0.30–0.99) years. After a median follow-up time of 5.36 (0.20–12.90) years, 59.3% experienced progressive disease (PD). 5y-PFS and -OS for the whole cohort were 38.2% and 73.1%. RELA - and YAP -fusion positive EP had significantly better OS than PF-A (5y-OS for PF-A: 55.9%; RELA 100%; YAP 100%; p=0.023). PFS was not significantly different. All but one patient with relapsed PF-A died despite multimodal salvage strategies. In contrast, patients with relapsing RELA - and YAP -fusion positive EP (n=5), survived with a combination of re-surgery and first or second local radiotherapy. CONCLUSION: In this cohort of infants <12 months, patients with PF-A had a significantly inferior OS compared to patients with RELA - and YAP -fusion positive EP. Salvage therapy was ineffective for patients with PF-A, whereas patients with can RELA - and YAP -fusion positive EP can be long-term survivors after PD. Therefore, subgroups-specific therapy should be discussed.